Innovative continuum of care to promote exclusive breast feeding in Pakistan: protocol of a pilot randomised controlled trial - Siham Sikander; Zahid Azam Chaudry; Tehmina Naz; Iqra Arshad; Aisha Zahoor; Mahum Javaid (BMJ Publishing Group, 2024)
Background Breastmilk being the ideal nutrition from birth to 2 years and beyond has many health benefits for both newborn and mothers. This study will assess the feasibility and acceptability of a continuum of care programme, which is a health facility and community based till 6 months post partum to encourage ideal breastfeeding practices.Methods and analysis A pilot randomised control trial having two-parallel arms of intervention and control groups was conducted in gynaecology and obstetrics department of Aziz Bhatti Shaheed Teaching Hospital with a community outreach component of 6 months. 50 women between 28 and 32 weeks of gestation fulfilling inclusion criteria will be allocated in 1:1 randomly into intervention and control groups through computer-generated random number generator software. 25 participants in intervention group will receive counselling and training on breast feeding during antenatal visits along with a family member of support by a trained female doctor within the hospital, at birth by a trained nurse and at home for 6 months by a trained lady health worker. It will be supported by reading materials and videos through a mobile phone WhatsApp application. The 25 participants in control group will receive the support already provided within the hospital and at home. The primary outcomes feasibility and acceptability will be determined at 6 months post partum from participants and providers by a semistructured questionnaire. The secondary outcomes are rates of infant early initiation and exclusive breast feeding at 2 weeks, 1, 3 and 6 months, Infant Feeding Attitude at 1 month and Breastfeeding Self-Efficacy at 3 months. Quantitative and qualitative data will be analysed via SPSS software V.20 and thematic analysis, respectively.Conclusion This pilot randomised controlled trial (RCT) will guide the interventions for the definite RCT.Ethics and dissemination Approved by institutional ethical committee, informed consent from all participants and results will be disseminated in peer-reviewed journal.Trial registration number NCT05951868.